2014
DOI: 10.1093/scan/nsu150
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin increases bias, but not accuracy, in face recognition line-ups

Abstract: Previous work indicates that intranasal inhalation of oxytocin improves face recognition skills, raising the possibility that it may be used in security settings. However, it is unclear whether oxytocin directly acts upon the core face-processing system itself or indirectly improves face recognition via affective or social salience mechanisms. In a double-blind procedure, 60 participants received either an oxytocin or placebo nasal spray before completing the One-in-Ten task-a standardized test of unfamiliar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…Given that this bias was not replicated in both face matching tasks, it is unclear how this phenomenon may be interpreted. Nonetheless, this finding contributes to the body of literature showing limited effects of enhancement techniques and motivation on face processing ability [ 10 , 15 , 19 ].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Given that this bias was not replicated in both face matching tasks, it is unclear how this phenomenon may be interpreted. Nonetheless, this finding contributes to the body of literature showing limited effects of enhancement techniques and motivation on face processing ability [ 10 , 15 , 19 ].…”
Section: Discussionsupporting
confidence: 55%
“…However, it is important to note that there is little evidence to suggest that typical perceivers can be successfully trained in facial image comparison, and it may be that the aforementioned experts are naturally better at unfamiliar face processing. Some studies have reported no training-related improvements at all [ 15 17 ], although recent investigations have noted minor enhancements with feedback [ 18 ] cf. [ 19 ] or when matching decisions are made in pairs [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Bate et al [] reported that participants' overall memory performance was not affected by Oxt, but it elicited a positive response bias, i.e., participants were more likely to make false‐positive recognition errors.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, memory-enhancing effects have been reported for faces regardless of emotion expression (Rimmele et al, 2009 ), only for faces with a positive expression (Guastella et al, 2008 ), or only for faces with neutral or negative expressions (Savaskan et al, 2008 ). In still other studies, there was no evidence for memory-enhancing oxytocin effects for faces at all (Di Simplicio et al, 2009 ; Herzmann et al, 2012 ; Bate et al, 2015 ). For example, Di Simplicio et al ( 2009 ) report no effect on actual memory performance, but only on emotional classifications of facial stimuli.…”
Section: Introductionmentioning
confidence: 89%
“…For example, Di Simplicio et al ( 2009 ) report no effect on actual memory performance, but only on emotional classifications of facial stimuli. Likewise, Bate et al ( 2015 ) found that oxytocin did not affect memory accuracy per se in a recognition memory test for faces, but rather induced more liberal responding, i.e., an enhanced general willingness to accept any stimulus in the memory test as previously seen.…”
Section: Introductionmentioning
confidence: 97%